Design with the sun passive solar architecture - Balibrera, Mario; Balibrera, Dana Evan; Danamar Film Productions; Bullfrog films ([Oley, PA ] : Bullfrog Films, 1979)
Shows passive solar homes and buildings across the country and describes innovative designs and building techniques that utilize passive solar principles
Title from title screen
Cinematography, Mario Balibrera, Clint Dougherty ; editor, Mario Balibrera
Keywords: Architecture and solar radiation -- United States; Architecture, Domestic -- United States